MENCERMATI POKOK AJARAN GEREJA & MENGURAI KONSEKWENSI BAGI PENDIDIKAN KRISTIANI: CATATAN-CATATAN KRITIS UNTUK GEREJA MASEHI ADVENT HARI KETUJUH - Stimson Hutagalung (Jurnal Koinonia, 2013)
Religious pluralism exist because of the many religions and beliefs adopted in this world. In this case, the Christian Education organized by the Seventh-day Adventist Church both in the church and education at schools and universities not only transfer the knowledge of science and technology but also motivate learners to practice it through IMTAK (faith piety), in order to cultivate good deeds which is the core of the doctrine or the teachings of the church itself. As an example of the ambivalence between the Adventist Church's teachings and practices, is the thinking that only members of the Adventist church alone are savevd when the church has never taught that way. Here is the role of Christian education, to educate students that everybody can be saved when they have faith in Jesus and His teachings.